Citizenship Education and the EFL Standards: A Critical Reflection (2017)
The reconfiguration of geographical and cultural boundaries has caused a growing concern among countries in regard to raising awareness of the importance of educating people to become “citizens of the world.” The language classroom seems to be the ideal place to incorporate the teaching and learning of global citizenship education, given its cross-cultural nature. This article intends to analyze the potential opportunities for the development of global citizenship education in the English as a foreign language classroom through a documentary analysis of the national standards and its connection to the national citizenship competences standards and the UNESCO global citizenship education topics and learning objectives. Finally, important recommendations are given to foster global citizenship in the English language classroom.